Pengaruh Relationship Marketing, Kualitas Produk, dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan - Ummah, Inayatul; Walyoto, Sri (Journal of Economics and Business Research (JUEBIR), 2024)
This research aims to determine the influence of relationship marketing, product quality, and customer satisfaction on customer loyalty in the Twenty Five Florist home industry in Boyolali District. This type of research in quantitative research. The number of samples used in this research was 129 respondents taken from each sub-district in Boyolali District. The sampling technique uses purposive sampling with the sample collection method via Google Form and distributing questionnaires offline. Data analysis techniques use SPSS 21. The research results show that the relationship marketing variable partially has no effect on customer loyalty. Product quality has a positive and significant effect on customer loyalty. Customer satisfaction has a positive and significant effect on customer loyalty. Then simultaneously relationship marketing, product quality, and customer satisfaction influence customer Loyalty in the Twenty Five Florist home industry in Boyolali.